2016
DOI: 10.1111/sed.12282
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the preservation of orbital forcing in peritidal carbonates

Abstract: Metre-scale cycles in ancient peritidal carbonate facies have long been thought to represent the product of shallow water carbonate accumulation under orbitally controlled sea-level oscillations. The theory remains somewhat controversial, however, and a contrasting view is that these cycles are the product of intrinsic, and perhaps random, processes. Owing to this debate, it is important to understand the conditions that do, or do not, favour the preservation of orbital forcing, and the precise stratigraphic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 58 publications
0
25
0
Order By: Relevance
“…For ancient carbonate platforms, similar observations were made suggesting that infill of accommodation space was a more random process, e.g., the Maiella platform margin (Central Italy; Eberli, 2013), the Latemar limestone platform (northern Italy; Kemp, Manen, Pollitt, & Burgess, 2016), and the Cambrian and Ordovician peritidal sequences exposed throughout the south-central Appalachians (Wilkinson, Diedrich, & Drummond, 1996). In these studies, unpredictable variations were found as variable or incomplete cycle thickness, variable cycle frequency, and absence of a shallowing-upward trend within the cycle (Eberli, 2013;Kemp et al, 2016;Wilkinson et al, 1996). Other uncertainties relate to the partial erosion of sediment infilling accommodation space during sea-level fall as well as facies-dependent variations in sediment compaction (Strasser, Pittet, Hillgärtner, & Pasquier, 1999).…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…For ancient carbonate platforms, similar observations were made suggesting that infill of accommodation space was a more random process, e.g., the Maiella platform margin (Central Italy; Eberli, 2013), the Latemar limestone platform (northern Italy; Kemp, Manen, Pollitt, & Burgess, 2016), and the Cambrian and Ordovician peritidal sequences exposed throughout the south-central Appalachians (Wilkinson, Diedrich, & Drummond, 1996). In these studies, unpredictable variations were found as variable or incomplete cycle thickness, variable cycle frequency, and absence of a shallowing-upward trend within the cycle (Eberli, 2013;Kemp et al, 2016;Wilkinson et al, 1996). Other uncertainties relate to the partial erosion of sediment infilling accommodation space during sea-level fall as well as facies-dependent variations in sediment compaction (Strasser, Pittet, Hillgärtner, & Pasquier, 1999).…”
Section: Introductionmentioning
confidence: 67%
“…Studies of the GBB as a modern example show that the Holocene sediment infill of the available accommodation space is a recent feature west of Andros Island (Maloof & Grotzinger, 2012) and the major part of the platform has remained unfilled (Bergman et al, 2010;Boss & Rasmussen, 1995). For ancient carbonate platforms, similar observations were made suggesting that infill of accommodation space was a more random process, e.g., the Maiella platform margin (Central Italy; Eberli, 2013), the Latemar limestone platform (northern Italy; Kemp, Manen, Pollitt, & Burgess, 2016), and the Cambrian and Ordovician peritidal sequences exposed throughout the south-central Appalachians (Wilkinson, Diedrich, & Drummond, 1996). In these studies, unpredictable variations were found as variable or incomplete cycle thickness, variable cycle frequency, and absence of a shallowing-upward trend within the cycle (Eberli, 2013;Kemp et al, 2016;Wilkinson et al, 1996).…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…This is modelled as a stochastic process to match the findings of Blanchon & Blakeway () (Fig. A) who determined a modal lag time of ca 1 to 2 kyr, with a distribution skewed towards shorter (<1 kyr) durations (see also Kemp et al ., ). Once initiated, accumulation is modelled as either positive (aggradational) or negative (erosional) at each time step.…”
Section: Methodsmentioning
confidence: 97%
“…Figure A illustrates the model, which is based largely on that presented in Kemp et al . () (MATLAB model code is available in Appendix ). In detail, when the platform is submerged, accumulation can occur, but it is subject to a lag time that reflects patchy (re)colonization of the platform surface by carbonate producers (Tipper, ).…”
Section: Methodsmentioning
confidence: 99%